Prototype Sistem Monitoring Real-Time Transformator Distribusi Berbasis IoT untuk Predictive Maintenance dan Notifikasi Gangguan - Djuma, Bartolomeus Rynaldi; Sari, Resi Dwi Jayanti Kartika; Sumarahinsih, Andrijani (IAI Nasional Laa Roiba Bogor, 2025)
Distribution transformers are important components in electrical systems that are susceptible to disturbances such as overload and overheating. To overcome the limitations of manual monitoring, this study developed a prototype of an Internet of Things (IoT)-based transformer monitoring system that is able to read voltage, current, temperature, and humidity in real-time, and provide automatic notification if there is a parameter deviation. The system is built using an ESP32 microcontroller connected to the ZMPT101B sensor for voltage, ACS712 for current, and DHT22 for temperature and humidity. Tests were carried out on a 220V/24V AC single-phase transformer with gradual load variations and different environmental scenarios. The test results showed that the ZMPT101B sensor had an average error of 0.06% against a multimeter, while the ACS712 showed an average error of 1.18% against a clamp meter. The DHT22 sensor recorded a total error of 4.81% for temperature and 5% for humidity compared to the HTC-1 measuring instrument. The system successfully sends notifications via the Blynk platform when the temperature exceeds 60°C or the current exceeds 4 A. With a fairly high level of accuracy and real-time monitoring capabilities, this system is considered suitable for use as a monitoring and predictive maintenance solution for small to medium-scale distribution transformers.